ASAS ITIKAD BAIK DALAM PERJANJIAN SEWA MENYEWA RUANGAN PERKANTORAN ANTARA PENYEWA DENGAN PEMILIK GEDUNG PT. SURYA DUMAI INDUSTRI TBK DI KOTA PEKANBARU - Hutabarat, Tio Dara Sabri; Firdaus, Firdaus; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The rental agreement for the Surya Dumai building space between PT. Surya Dumai Industri Tbk with tenants regarding the rights and obligations of tenants and owners are regulated in chapter II regarding the Lease Agreement. In chapter IV concerning Leases which states that: "If the tenant renews the lease agreement, the lessee must provide written notification no later than 3 (three) months before the Agreement ends but not sooner than 6 (six) months before the Agreement ends". However, one of the lessee parties does the interpretation to terminate the contract outside the agreement. After 3 (three) months of serving the lease, the tenant terminated the contract without written notification to Surya Dumai. In this case, the lessee has violated the provisions contained in chapter IV concerning Leases.This type of research is empirical juridical research. Empirical juridical research is the form or pouring of the results of research on real laws or according to the realities that live in society. The research location is PT. Surya Dumai Industri Group, which is located at Jl. Jendral Sudirman Number 395, Pekanbaru. The population and sample in this study are tenant relations and administration as well as tenants for Gedung Surya Dumai. Data collection techniques in this study were interviews and literature review.The results of this study are as follows the implementation of the lease agreement of PT. Surya Dumai Industri Tbk, between tenants and building owners is not in accordance with the principle of good faith. In particular, in the implementation of the office space tenant's obligations to the building owner, the tenant is not in good faith in carrying out the office space lease, causing losses to the building owner in implementing the lease agreement. The form of default is being late in fulfilling the achievements. And also the tenant does not have good intentions in resolving the problems that arise in the implementation of this lease agreement, where there is no communication between the tenant and the building owner while the lease agreement is carried out. Efforts made to improve the principle of good faith in the lease agreement for office space are: negotiation or deliberation efforts, providing warning letters to the tenants, and collection efforts.Keywords: good faith principle, agreement, lease